The Diagnostic Dilemma of Acute Granulomatous Hepatitis in a Patient With Crohn's Disease: A Case Report and Review of Literature - Eltaib Saad MD; Mohamed Agab MD; Emre Can Ozcekirdek MD; Abdalaziz Awadelkarim MD; Isra Idris MD (SAGE Publishing, 2022)
Liver involvement is not an uncommon extraintestinal manifestation of inflammatory bowel disease (IBD). IBD-associated liver diseases may have a variety of etiopathogenetic origins (including shared autoimmune pathogenesis, the effect of chronic inflammatory status, and adverse effects of drugs). Nevertheless, acute granulomatous hepatitis in the setting of Crohn's disease (CD) is a rare clinical entity. It warrants, however, a careful assessment as both clinical and pathological features of Crohn's-associated granulomatous hepatitis closely mimic extrapulmonary hepatic sarcoidosis, with considerable overlaps between the 2 diseases, which certainly makes a definitive diagnosis quite challenging. It is crucial to exclude infectious etiologies during the evaluation of acute granulomatous hepatitis, as inappropriate immunosuppressive treatment may cause a systemic flare-up of an underlying liver infection. We report a rare case of a 35-year-old female with a history of CD who presented with recurrent fevers, acute abdominal pain, and cholestasis. She was found to have acute hepatitis with noncaseating granulomas on liver biopsy. A comprehensive diagnostic workup did not ultimately prove a specific etiological culprit. The patient was treated with oral corticosteroids, and she demonstrated a positive clinical and laboratory response to the treatment. Our case highlights the diagnostic dilemma of acute granulomatous hepatitis in the setting of co-existent CD with a multisystemic syndrome. Granulomatous hepatitis represents a relatively rare manifestation of both extraintestinal CD and extrapulmonary sarcoidosis, with potential difficulties discriminating between the 2 entities on many occasions. The case also demonstrates the value of an interdisciplinary approach in the context of multisystemic disease to achieve the best outcome.